2016
DOI: 10.1038/srep20995
|View full text |Cite
|
Sign up to set email alerts
|

Structure and biological function of ENPP6, a choline-specific glycerophosphodiester-phosphodiesterase

Abstract: Choline is an essential nutrient for all living cells and is produced extracellularly by sequential degradation of phosphatidylcholine (PC). However, little is known about how choline is produced extracellularly. Here, we report that ENPP6, a choline-specific phosphodiesterase, hydrolyzes glycerophosphocholine (GPC), a degradation product of PC, as a physiological substrate and participates in choline metabolism. ENPP6 is highly expressed in liver sinusoidal endothelial cells and developing oligodendrocytes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 35 publications
2
68
0
Order By: Relevance
“…In a follow-up study, the ecto-enzyme Enpp6 was also identified as an encoding marker of newly forming OLs during adult myelination [29]. Mechanistically, Enpp6, as phosphodiesterase, likely has a role in lipid metabolism during myelin formation [30] and might be required to initiate myelination rapidly in response to differentiation-inducing signals. Consequently, it has been shown that conditional deletion of Myrf in NG2-glia prevents the development of new Enpp6 + OLs which leads to impaired learning [29].…”
Section: Oligodendrocytes: Beyond Developmental Myelination and Remyementioning
confidence: 99%
“…In a follow-up study, the ecto-enzyme Enpp6 was also identified as an encoding marker of newly forming OLs during adult myelination [29]. Mechanistically, Enpp6, as phosphodiesterase, likely has a role in lipid metabolism during myelin formation [30] and might be required to initiate myelination rapidly in response to differentiation-inducing signals. Consequently, it has been shown that conditional deletion of Myrf in NG2-glia prevents the development of new Enpp6 + OLs which leads to impaired learning [29].…”
Section: Oligodendrocytes: Beyond Developmental Myelination and Remyementioning
confidence: 99%
“…1A). The crystal structures of NPP1 [3,4], NPP2 [7,8], NPP4 [6], NPP6 [9], and NPP7 [10] are known, and the secondary structure elements are well-conserved within the catalytic domain (Fig. This a-b-a fold classifies the protein into the alkaline phosphatase superfamily (CATH ID: 3.40.720.10).…”
Section: Resultsmentioning
confidence: 99%
“…NPP1 is located on the surface of osteoblasts and chondrocytes where it cleaves NTPs to generate pyrophosphate, an inhibitor of bone mineralization [3,4]. NPP6 participates in choline metabolism, with glycerophosphocholine as the proposed substrate [9], whereas NPP7 (alkaline sphingomyelinase) digests dietary sphingomyelin in the intestines [10]. NPP4 is present on brain vascular endothelium and participates in hemostasis by converting diadenosine triphosphate to ADP, which induces platelet aggregation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mog is located on the surface of oligodendrocytes and myelin sheaths (Brunner, Lassmann, Waehneldt, Matthieu, & Linington, ). Enpp6 is required for the development of myelin sheath (Morita et al, ). Mobp plays a role in myelin compaction or stabilization (Montague, McCallion, Davies, & Griffiths, ).…”
Section: Discussionmentioning
confidence: 99%